View Factors in Horizontal Plane Fixed-Mode Solar PV Fields - Nassar, Yasser F.; El-Khozondar, Hala J.; Belhaj, Said O.; Alsadi, Samer Y.; Abuhamoud, Nassir M. (Frontiers in Energy Research, 2022)
In solar PV fields, solar photovoltaic panels are typically arranged in parallel rows one after the other. This arrangement introduces variations in the distribution of solar irradiance over the entire field, compared to measurements made at meteorological weather stations and data obtained from solar radiation databases. This is due to the difference in the view factors between the rows of the solar PV field and a single reference surface, as well as the presence of shade on rear rows and in the space separating the rows. These phenomena combined will reduce the energy yield of a solar PV field. Accurate estimation of solar radiation on solar fields requires knowledge of the sky, ground, and rear surface of the preceding row view factors, and an estimation of the time and space occupied by the row’s shadow. Prior literature has addressed this issue using two-dimensional (2D) techniques such as Crossed-Strings Method, which this study proved to be inaccurate particularly in the case of Rooftop solar PV fields. This study uses a novel three-dimensional (3D) analytical and numerical analysis to determine the view factors associated with solar fields using hourly solar irradiance data acquired from Solar-GIS for the period 2007-2020, including global, beam, and sky diffuse irradiance components on horizontal plane. The study uses both isotropic and anisotropic transposition analyses to determine solar irradiance incident on the solar field with varying tilt angles of solar panels and distance separating the rows.